Partial fiscal decentralization - Jan Keith Brueckner (Center for Economic Studies and ifo Institute (CESifo), 2007)
The fiscal decentralization impulse now sweeping the world often leads to partial decentralization, where subnational governments are funded by central transfers, rather than leading to full local autonomy. Despite the practical important of this arrangement, the literature contains no economic analysis of a partial decentralization regime in a Tiebout-style model. This paper provides such an analysis, relying on the key assumption that public-good provision requires effort on the part of government officials. By choosing different degrees of effort, localities can then provide different public-good levels even when a fixed, common transfer constrains them to spend the same amount. A number of useful results are derived.
Keywords: H1; H7; 330; Fiskalische Dezentralisierung; Öffentliches Gut; Institutioneller Wettbewerb; Theorie